Teaching English in Urban Sri Lanka The Case of Four Government Schools in Colombo - Karunaratne, Iresha Madhavi (My University, 2008)
This paper examines the effectiveness of the teaching methodology adopted for teaching English in four government schools in Colombo. The curriculum specifies Communicative Language Teaching (CLT) as the teaching methodology that should be used in Sri Lankan schools for teaching English. The data gathered in this study was analysed in relation to three the main principles of CLT, namely use of a variety of teaching materials, reasonable use of the students’ mother tongue and a pupil-centred teaching approach. It was observed that the textbook was the sole source of teaching material and classroom activity and that teachers and students depended excessively on the mother tongue during classroom activities. Furthermore, it was also observed that the classrooms were more teacher-centred than pupil-centred. Students were observed to be more comfortable with this ‘dominant approach’ adopted by teachers. These circumstances hindered the possibility of carrying out an effective communicative classroom as idealised by the proponents of CLT. Teachers’ lack of English proficiency and the national examination system which focuses solely on students’ reading and writing skills were identified as causing these classroom circumstances. These findings imply a need to improve teacher-training programs and to change the national examination system.